Hidden magnetism in the paramagnetic phase of EuTiO3. (24th November 2015) - Gregori, G; Köhler, J; Scott, J F; Bussmann-Holder, A
Abstract: EuTiO3 is investigated experimentally by temperature dependent conductivity and dielectric constant measurements. Both data sets evidence a crossover behavior in their temperature dependence around T * 200 K indicating a change of the electrical and magnetic behavior of EuTiO3 as already observed by muon spin rotation ( μ SR) measurements. Around T ′ = 80 K an additional anomaly appears which is consistent with previous resonant ultrasound spectroscopy (RUS) data. By applying a magnetic field (1.2 T at room temperature) the bulk conductivity is anomalously enhanced by more than one order of magnitude. The bulk dielectric constant ε r decreases with increasing temperature and is enhanced by the magnetic field by up to 22%. All data reveal a substantial hysteresis which is diminished in a magnetic field. The unusual magnetic field dependence of all quantities is suggested to stem from magnetically active domain walls which are mobile between the structural phase transition temperature ( T S = 282 K) and T * and are pinned below it.